Alcohol pouring practices among 65- to 74-year-olds in Western Australi - Wilkinson, Celia; Allsop, Steven; Chikritzhs, Tanya (Informa Healthcare, 2010)
Introduction and Aims. Alcohol pouring practices have relevance to the validity of self-reported alcohol consumption. However, little research has focused on older populations nor investigated relationships between volumes poured and participants' estimations of beverages in terms of Australian standard drinks. The aim of this study was to address these issues. Design and Methods. Interviews were conducted (in participants' homes) with 844 current drinkers, aged 65–74 years, from Perth, Western Australia. Participants poured their ‘usual’ serving of alcohol into their ‘usual’ drinking vessel and were asked questions regarding the volumes poured. Results. Older men poured drinks that were 32% larger than a standard drink (10 g of ethanol). The comparable figure for older women was 16%. However, over 25% of all men and 20% of all women indicated they would not record (in a self-report assessment of consumption) the amount poured as one standard drink. Despite participants making corrections, men and women still underestimated amounts poured (men by 23% and women by 16%). Discussion and Conclusions. As with younger populations, older people pour drinks that are, on average, larger than standard drinks. To increase the accuracy of self-reported consumption, it is recommended that researchers consider pouring practices and people's perceptions of alcohol volumes poured in relation to a standard drink. Further research on this issue may reduce the discrepancy between self-reported levels of consumption and national per capita alcohol sales.